Hygrothermal analysis of a wall isolated from the inside: the potential of dynamic hygrothermal simulation. Issue 1 (October 2021) - Panico, S; Larcher, M; Troi, A; Codreanu, I; Baglivo, C; Congedo, P M
Abstract: Hygrothermal simulations are expected to provide powerful support to the design process in the context of energy retrofit of historic buildings and prevent the moisture-related damages. They can be used to predict the hygrothermal behaviour of the building in detail and exclude the occurrence of moisture related damages, such as mould formation or material degradation. However, these simulations require various input data related to materials and boundary conditions, which are often difficult to find during the design phase. In this article we analyse the potential of hygrothermal simulations in predicting the hygrothermal behaviour of an internally insulated wall, even with limited information on the hygrothermal properties of the materials composing the historical wall. The quality of the simulation's results is evaluated through a comparison with monitored data. The numerical model is calibrated to maximise the agreement with the monitored data. The considered case study is a historical building located nearby Bolzano (Northern Italy). The monitoring system is installed with the aim of analysing temperature and relative humidity profiles within the construction. In addition, the climatic boundary conditions are measured both inside and outside the building, including temperature, relative humidity, driving rain and solar radiation. The numerical simulation of the wall under analysis is performed with the software DELPHIN.